Preparation method of composite aerogel containing MXene

By combining MXene with nanocellulose and modified polyvinyl alcohol, a composite aerogel with excellent wave absorption and sound absorption properties was prepared, which solved the problem of insufficient wave absorption and mechanical properties and easy oxidation of MXene materials, and achieved high efficiency Electromagnetic wave absorption and sound wave absorption, and improve the material's antioxidant performance and service life.

CN119144043AActive Publication Date: 2024-12-17SHAANXI UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411311988.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-17
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

The existing MXene materials have shortcomings in electromagnetic wave absorption and mechanical properties, and are prone to oxidation, resulting in a decrease in wave absorption and sound absorption performance. There are few researches on existing wave absorption and sound absorption composite materials.

Method used

MXene is combined with nanocellulose and modified polyvinyl alcohol to prepare composite aerogels with regular three-dimensional network structures through directional freezing, increasing antioxidant performance, and optimizing wave and sound absorption performance through structural design.

Benefits of technology

It realizes the efficient absorption of electromagnetic and sound waves of composite materials, with antioxidant properties, compressible rebound and lightweight characteristics, extends service life and reduces raw material costs and preparation complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a preparation method of MXene-containing composite aerogel, which comprises the following steps: centrifuging and concentrating to obtain few-layer MXene suspensions with different concentrations; the preparation method comprises the following steps: under the protection of nitrogen, performing acetalation modification on polyvinyl alcohol to obtain modified polyvinyl alcohol with catechol groups; the preparation method comprises the following steps: dissolving modified polyvinyl alcohol in water to obtain a modified polyvinyl alcohol solution, sequentially adding a nanocellulose aqueous solution and a few-layer MXene dispersion liquid, uniformly stirring and mixing, pouring a mixed solution into a mold, directionally freezing by liquid nitrogen, and drying in vacuum to obtain the MXene-containing composite aerogel. The material is low in raw material cost and simple in preparation process, and has a huge application prospect in the fields of electromagnetic wave absorption and sound absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of application of MXene materials in aerogels, and in particular relates to a method for preparing a composite aerogel containing MXene. Background Art

[0002] With the continuous development of electronic technology, human production and daily life have become more convenient. However, the electromagnetic wave pollution that comes with it may not only affect the normal operation of electronic equipment and human health, but also threaten military security in the military field. Industrial development is also accompanied by problems such as noise pollution. Therefore, the development of composite materials with wave-absorbing and sound-absorbing properties is of great significance. Through existing research, it is found that aerogel materials with porous structures not only show excellent wave-absorbing properties, but also have lightweight and high-strength mechanical properties, which meet the current development needs of wave-absorbing materials in terms of "thin, light, wide and strong", and are also widely used in the field of sound absorption. However, there are currently few studies on composite materials that have both wave-absorbing and sound-absorbing properties, and the service life of wave-absorbing materials is also a difficult problem in research.

[0003] As a new type of two-dimensional nanomaterial, MXene has good conductivity, hydrophilicity, high specific surface area and rich surface functional groups. It can be added to composite aerogels as a conductive filler to enhance its dielectric loss performance and achieve electromagnetic wave absorption. Existing studies have pointed out that the absorption capacity of MXene alone as an absorbing material is relatively limited, which is manifested in low absorption intensity and small effective absorption width. Therefore, its absorbing performance still needs to be optimized. In addition, the mechanical properties of MXene materials are poor and they are easily oxidized. Long-term repeated use will lead to a decrease in absorbing and sound absorbing performance. Compounding MXene with other materials can help improve its mechanical properties and absorbing performance. Nanocellulose has the advantages of green renewability, biocompatibility and degradability, and is a leader in environmentally friendly materials. Composite aerogel materials based on cellulose show high economic and environmental value in the fields of sound absorption, wave absorption, building thermal insulation, etc., and can meet the structural requirements of absorbing materials and sound absorbing materials at the same time. At the same time, combined with the application of composite aerogel materials in the fields of wave absorption and sound absorption in current literature, wave-absorbing and sound-absorbing composite materials are prepared from the perspective of structural design, and the coordinated optimization of wave absorption and sound absorption performance is achieved.

[0004] Therefore, MXene is compounded with nanocellulose aqueous solution to prepare a composite aerogel with good wave-absorbing properties, and its sound-absorbing and mechanical properties are improved through structural design, and its antioxidant properties are improved by adding modified polyvinyl alcohol. This research is very important for the preparation and application of new wave-absorbing and sound-absorbing composite aerogels. Summary of the invention

[0005] The present invention provides a method for preparing a compressible, oxidation-resistant cellulose-based wave-absorbing and sound-absorbing MXene composite aerogel.

[0006] In order to solve the above technical problems, the technical solutions provided by the present invention are as follows:

[0007] A method for preparing a composite aerogel containing MXene comprises the following steps:

[0008] The few-layer MXene suspension is centrifuged and concentrated to obtain few-layer MXene dispersions of different concentrations;

[0009] 3,4-dihydroxybenzaldehyde and p-toluenesulfonic acid monohydrate are subjected to acetalization reaction under nitrogen protection and elevated temperature conditions to obtain a catechol-modified polyvinyl alcohol solid modified with catechol, which is dissolved to obtain a catechol-modified polyvinyl alcohol solution;

[0010] The cellulose-based solution was added to the catechol-modified polyvinyl alcohol solution and stirred evenly, and then added to the few-layer MXene solution. After stirring, it was passed through a mold and directionally frozen with liquid nitrogen. After drying, a composite aerogel containing MXene was obtained.

[0011] Furthermore, the method also includes the preparation of a few-layer MXene suspension, which is prepared by etching a MAX phase precursor with LiF-HCl, wherein the MAX phase precursor includes Ti3C2T X Solution, Ti3N2T X Solution, Ti3CNT X Solution or Ti2CT X One or more of the solutions.

[0012] Furthermore, the centrifugal speed during concentration of the few-layer MXene suspension is 10,000 rpm; the centrifugation time is 10-20 min; and the concentration of the few-layer MXene suspension obtained after centrifugation and concentration is 2-10 mg / mL.

[0013] Furthermore, the preparation of the catechol-modified polyvinyl alcohol is specifically to add polyvinyl alcohol powder into dimethyl sulfone, continuously stir and heat it to make it completely dissolved, cool it to room temperature, and then add 3,4-dihydroxybenzaldehyde and p-toluenesulfonic acid monohydrate to carry out acetalization reaction.

[0014] Furthermore, the mass ratio of the polyvinyl alcohol, 3,4-dihydroxybenzaldehyde and p-toluenesulfonic acid monohydrate is 1:(0.07-0.08):(0.2-0.3); and the dissolution temperature of the polyvinyl alcohol is 80°C.

[0015] Furthermore, after the acetalization reaction, the catechol-modified polyvinyl alcohol solid is obtained after acetone precipitation and vacuum drying.

[0016] Furthermore, the modified polyvinyl alcohol is dissolved in deionized water at 80° C. to obtain the modified polyvinyl alcohol solution.

[0017] Furthermore, the mass fraction of the cellulose-based solution is 1%-2%; the freeze-drying temperature is -50 to -60°C; and the freeze-drying time is 48 to 72 hours.

[0018] Furthermore, the mass ratio of the nanocellulose, catechol-modified polyvinyl alcohol and MXene is 1:1:2.

[0019] The present invention has the following beneficial effects:

[0020] The present invention uses cellulose aerogel as a carrier to load the conductive material, which not only has the characteristics of light weight of traditional aerogel materials, but also has the advantages of renewable and degradable biomaterials and good biocompatibility.

[0021] The present invention uses MXene as a conductive filler and mixes it with cellulose, and prepares a composite aerogel with a regular three-dimensional network structure through directional freezing, while absorbing electromagnetic waves and sound waves.

[0022] The present invention adds catechol-modified polyvinyl alcohol, and the interaction between the catechol group on the modified polyvinyl alcohol and the surface of MXene inhibits the oxidation of MXene, so that the material has certain antioxidant properties and improves the service life of the composite aerogel.

[0023] The compressible, anti-oxidation cellulose-based wave-absorbing and sound-absorbing material provided by the present invention is prepared by using cellulose as a matrix, MXene as a conductive filler, and adding catechol-modified polyvinyl alcohol, directional freezing with liquid nitrogen, and finally freeze-drying; the material has excellent electromagnetic wave and sound wave absorption performance, and also has the characteristics of anti-oxidation, compressible rebound, light weight, etc. The raw material cost of the present invention is low and the preparation process is simple, so it has great application prospects in the field of electromagnetic wave and sound wave absorption. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0025] Figure 1a This is a sample photo of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 3;

[0026] Figure 1bThis is a scanning electron microscope image of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 3 at 100 microns;

[0027] Figure 1c This is a scanning electron microscope image of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 3 at 50 microns;

[0028] Figure 1d This is a scanning electron microscope image of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 3 at 20 microns;

[0029] Figure 2a Schematic diagram of the microwave absorption performance of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 1;

[0030] Figure 2b Schematic diagram of the microwave absorption performance of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 2;

[0031] Figure 2c Schematic diagram of the microwave absorption performance of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 3;

[0032] Figure 2d Schematic diagram of the microwave absorption performance of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 4;

[0033] Figure 2e Schematic diagram of the microwave absorption performance of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 5;

[0034] Figure 3 This is a comparison chart of the sound absorption performance of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogels prepared in Example 1, Example 2, Example 3, Example 4, and Example 5;

[0035] Figure 4a The X-ray diffraction pattern and 30-day absorption performance comparison diagram of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 3;

[0036] Figure 4b This is a graph showing the microwave absorption performance of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 3 after being placed in the air for 10 days;

[0037] Figure 4cThis is a graph showing the wave absorption performance of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 3 after being placed in the air for 20 days;

[0038] Figure 4d This is a graph showing the wave absorption performance of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 3 after being placed in the air for 30 days;

[0039] Figure 4e This is a graph showing the wave absorption performance of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 3 after being placed in the air for 70 days;

[0040] Figure 5a Schematic diagram of the compression rebound performance of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 5;

[0041] Figure 5b MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 5 at 10%, 20% and 30% strains are stress-strain diagrams;

[0042] Figure 5c This is a stress-strain diagram of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 5 after 800 compression-release cycles at 20% strain;

[0043] Figure 5d This is a graph showing the retention rate of the original compressive strength of the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared in Example 5 after 800 compression-release cycles at 20% strain. DETAILED DESCRIPTION

[0044] The present invention is described in detail below in conjunction with various embodiments, but it should be noted that these embodiments are not limitations of the present invention, and any equivalent transformations or substitutions in functions, methods, or structures made by ordinary technicians in the field based on these embodiments are all within the scope of protection of the present invention.

[0045] The object of the present invention is to produce a method for producing a compressible, oxidation-resistant cellulose-based MXene-containing composite aerogel having wave-absorbing and sound-absorbing properties, comprising the following steps:

[0046] (1) Concentration of few-layer MXene suspensions.

[0047] The few-layer MXene suspension with a certain solid content was centrifuged at 10,000 rpm for 10 min, and part of the supernatant was poured out and shaken evenly.

[0048] According to the solid content of the few-layer structure MXene suspension and the volume of the supernatant to be poured off, the solid content of the MXene suspension is controlled to be 2 to 10 mg / mL.

[0049] (2) Preparation of catechol-modified polyvinyl alcohol.

[0050] Add polyvinyl alcohol powder to dimethyl sulfone (DMSO), stir continuously and heat it up to completely dissolve it. After cooling to room temperature, add a certain amount of 3,4-dihydroxybenzaldehyde (DBA) and p-toluenesulfonic acid monohydrate (TsOH), and carry out acetalization reaction under nitrogen protection and heating conditions. The mixture is cooled to room temperature, precipitated in acetone twice, and the precipitate is vacuum dried under certain conditions to obtain catechol-modified polyvinyl alcohol solid. Dissolve the synthesized catechol-modified polyvinyl alcohol in deionized water and completely dissolve it under heating conditions to obtain a catechol-modified polyvinyl alcohol solution.

[0051] The mass ratio of the polyvinyl alcohol, 3,4-dihydroxybenzaldehyde and p-toluenesulfonic acid monohydrate is 1:(0.07-0.08):(0.2-0.3); the dissolution temperature of the polyvinyl alcohol is 80°C; the acetalization reaction temperature is 80°C; the acetalization reaction time is 12h; and the vacuum drying temperature is 45°C.

[0052] (3) Preparation of MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel.

[0053] The cellulose-based solution was added to the catechol-modified polyvinyl alcohol solution in step 2 and stirred evenly. The MXene nanodispersion was added to the mixed solution and stirred evenly, and then the solution was placed in a mold and directionally frozen with liquid nitrogen, and then placed in a freeze dryer for freeze drying to obtain MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel.

[0054] In the step (3), the cellulose-based raw material may be one of nanocellulose and carboxylated nanocellulose.

[0055] The solid content of the cellulose-based solution is 1% to 2%; the freeze-drying temperature is -50 to -60°C; and the freeze-drying time is 48 to 72 hours.

[0056] In the step (3), the mass ratio of the nanocellulose, catechol-modified polyvinyl alcohol and MXene is 1:1:2.

[0057] The preparation method of the present invention is prepared by using a compressible, anti-oxidation cellulose-based wave-absorbing and sound-absorbing material with nanofibers as a support, MXene as a conductive filler, and catechol-modified polyvinyl alcohol as an antioxidant. The electromagnetic wave absorption performance and sound absorption performance of the composite material can be regulated and optimized by adjusting the MXene content; the prepared directional three-dimensional network structure has good compression rebound performance and can recover to its original state after being compressed hundreds of times; the catechol group on the modified polyvinyl alcohol can effectively inhibit the oxidation of MXene, so that the material has excellent anti-oxidation performance.

[0058] The invention has low raw material cost and simple preparation process, and has great application prospects in the fields of electromagnetic wave absorption and sound absorption.

[0059] Example 1

[0060] (1) The few-layer MXene suspension with a certain solid content was centrifuged at 10000 rpm for 10 min, and part of the supernatant was poured out and shaken evenly to obtain a stable and uniform black suspension. According to the solid content of the few-layer MXene suspension, the volume of the supernatant was adjusted to obtain a few-layer MXene suspension with a concentration of 2 mg / mL.

[0061] (2) Add 1g of polyvinyl alcohol powder to 10mL of dimethyl sulfone (DMSO) and stir at 80°C to completely dissolve it. After cooling to room temperature, add 75mg of 3,4-dihydroxybenzaldehyde (DBA) and 25mg of p-toluenesulfonic acid monohydrate (TsOH), and stir the reaction at 80°C for 12h under nitrogen protection. After the reaction is completed, the mixture is cooled to room temperature, and acetone is added to obtain a precipitate, which is vacuum dried at 45°C for 30min to obtain a catechol-modified polyvinyl alcohol solid. The synthesized catechol-modified polyvinyl alcohol is dissolved in deionized water, stirred at 90°C for 1h, and cooled to room temperature to obtain a 2% catechol-modified polyvinyl alcohol solution.

[0062] (3) Take 2g of 2% catechol-modified polyvinyl alcohol solution, add 2% nanocellulose at a mass ratio of 1:1 to catechol-modified polyvinyl alcohol, and stir evenly. Add 2mg / mL MXene dispersion at a mass ratio of 1:1 to the mixture to the mixed solution, stir evenly, then put the solution into a mold and freeze it with liquid nitrogen for 2 minutes, and then put it into a freeze dryer at a temperature of -58°C for freeze drying for 48 hours to obtain MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel.

[0063] The composite aerogel prepared in the embodiment of the present invention is tested for wave absorption and sound absorption performance. The wave absorption performance exhibited in the X-band is as follows: Figure 2aAs shown in FIG. 1 , the reflection coefficient of the film with a thickness of 13.15 mm can reach a minimum of -15.66 dB, which indicates that the invention has a certain wave absorption performance; the sound absorption performance exhibited in the frequency range of 1000 Hz-6300 Hz is as follows Figure 3 As shown, at this time, for a sample with a thickness of 30 mm, the sound absorption coefficient is greater than 0.2 dB, which indicates that the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared by the present invention has good sound absorption performance.

[0064] Example 2

[0065] (1) The few-layer MXene suspension with a certain solid content was centrifuged at 10000 rpm for 10 min, and part of the supernatant was poured out and shaken evenly to obtain a stable and uniform black suspension. According to the solid content of the few-layer MXene suspension, the volume of the supernatant was adjusted to obtain a few-layer MXene suspension with a concentration of 4 mg / mL.

[0066] (2) Add 1g of polyvinyl alcohol powder to 10mL of dimethyl sulfone (DMSO) and stir at 80°C to completely dissolve it. After cooling to room temperature, add 75mg of 3,4-dihydroxybenzaldehyde (DBA) and 25mg of p-toluenesulfonic acid monohydrate (TsOH), and stir the reaction at 80°C for 12h under nitrogen protection. After the reaction is completed, the mixture is cooled to room temperature, and acetone is added to obtain a precipitate, which is vacuum dried at 45°C for 30min to obtain a catechol-modified polyvinyl alcohol solid. The synthesized catechol-modified polyvinyl alcohol is dissolved in deionized water, stirred at 90°C for 1h, and cooled to room temperature to obtain a 2% catechol-modified polyvinyl alcohol solution.

[0067] (3) Take 2g of 2% catechol-modified polyvinyl alcohol solution, add 2% nanocellulose at a mass ratio of 1:1 to catechol-modified polyvinyl alcohol, and stir evenly. Add 4mg / mL MXene dispersion at a mass ratio of 1:1 to the mixture to the mixed solution, stir evenly, then put the solution into a mold and freeze it with liquid nitrogen for 5 minutes, and then put it into a freeze dryer at a temperature of -55°C for freeze drying for 48 hours to obtain MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel.

[0068] The composite aerogel prepared in the embodiment of the present invention is tested for wave absorption and sound absorption performance. The wave absorption performance exhibited in the X-band is as follows: Figure 2b As shown in FIG. 1 , the reflection coefficient of the film with a thickness of 2.45 mm can reach a minimum of -37.87 dB, which shows that the invention has excellent wave absorption performance; the sound absorption performance exhibited in the frequency range of 1000 Hz-6300 Hz is as follows Figure 3As shown, the sound absorption coefficient of the sample with a thickness of 30 mm is greater than 0.2 dB, which indicates that the invention has good sound absorption performance.

[0069] Example 3

[0070] (1) The few-layer MXene suspension with a certain solid content was centrifuged at 10000 rpm for 10 min, and part of the supernatant was poured out and shaken evenly to obtain a stable and uniform black suspension. According to the solid content of the few-layer MXene suspension, the volume of the supernatant was adjusted to obtain a few-layer MXene suspension with a concentration of 6 mg / mL.

[0071] (2) Add 1g of polyvinyl alcohol powder to 10mL of dimethyl sulfone (DMSO) and stir at 80°C to completely dissolve it. After cooling to room temperature, add 75mg of 3,4-dihydroxybenzaldehyde (DBA) and 25mg of p-toluenesulfonic acid monohydrate (TsOH), and stir the reaction at 80°C for 12h under nitrogen protection. After the reaction is completed, the mixture is cooled to room temperature, and acetone is added to obtain a precipitate, which is vacuum dried at 45°C for 30min to obtain a catechol-modified polyvinyl alcohol solid. The synthesized catechol-modified polyvinyl alcohol is dissolved in deionized water, stirred at 90°C for 1h, and cooled to room temperature to obtain a 2% catechol-modified polyvinyl alcohol solution.

[0072] (3) Take 2g of 2% catechol-modified polyvinyl alcohol solution, add 2% nanocellulose at a mass ratio of 1:1 to catechol-modified polyvinyl alcohol, and stir evenly. Add 6mg / mL MXene dispersion at a mass ratio of 1:1 to the mixture to the mixed solution, stir evenly, then put the solution into a mold and freeze it with liquid nitrogen for 3 minutes, and then put it into a freeze dryer at a temperature of -60°C for freeze drying for 48 hours to obtain MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel.

[0073] pass Figure 1a-1d From the photographs and scanning electron microscope images, it can be seen that the prepared MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel has a layered structure. In other words, Figure 1 shows that the aerogel has a regular layered structure in terms of morphology. This layered structure is related to good wave and sound absorption performance, and no further conclusions can be drawn directly. Further observation is needed for verification and demonstration.

[0074] And through Figure 2c and Figure 3 It can be clearly seen that the performance verification in this embodiment, specifically, by testing the wave absorption performance and sound absorption performance of the composite aerogel prepared in this embodiment, the wave absorption performance displayed in the X-band is as follows Figure 2cAs shown, it can be seen that the reflection coefficient of the 2.8mm thickness can reach a minimum of -46.85dB, and the effective absorption bandwidth can cover the entire X-band (8.2-12.4GHz), which shows that the invention has excellent wave absorption performance; the sound absorption performance displayed in the frequency range of 1000Hz-6300Hz is as follows Figure 3 As shown, the sound absorption coefficient of the sample with a thickness of 30 mm is greater than 0.2 dB, which indicates that the invention has good sound absorption performance.

[0075] The composite aerogel prepared in the embodiment of the present invention was tested for life span. Figure 4a As shown in the figure, after the CNF / PVA-CA / MXene-6 composite aerogel was placed at room temperature for 70 days, the characteristic peak of MXene (~6.1°) could still be observed through XRD testing, which indicates that catechol-modified polyvinyl alcohol prevented the oxidation of MXene in the composite aerogel, so that its microwave absorption performance was retained. Figure 4b ~e. After being placed at room temperature for 70 days, the effective absorption bandwidth of the CNF / PVA-CA / MXene-6 composite aerogel can cover the entire X-band (8.2-12.4 GHz), and its minimum reflection coefficient at 2.65 mm can reach -55.95 dB, which indicates that the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel of this invention has excellent stability in wave absorption performance.

[0076] Example 4

[0077] (1) The few-layer MXene suspension with a certain solid content was centrifuged at 10000 rpm for 10 min, and part of the supernatant was poured out and shaken evenly to obtain a stable and uniform black suspension. According to the solid content of the few-layer MXene suspension, the volume of the supernatant was adjusted to obtain a few-layer MXene suspension with a concentration of 8 mg / mL.

[0078] (2) Add 1g of polyvinyl alcohol powder to 10mL of dimethyl sulfone (DMSO) and stir at 80°C to completely dissolve it. After cooling to room temperature, add 75mg of 3,4-dihydroxybenzaldehyde (DBA) and 25mg of p-toluenesulfonic acid monohydrate (TsOH), and stir the reaction at 80°C for 12h under nitrogen protection. After the reaction is completed, the mixture is cooled to room temperature, and acetone is added to obtain a precipitate, which is vacuum dried at 45°C for 30min to obtain a catechol-modified polyvinyl alcohol solid. The synthesized catechol-modified polyvinyl alcohol is dissolved in deionized water, stirred at 90°C for 1h, and cooled to room temperature to obtain a 2% catechol-modified polyvinyl alcohol solution.

[0079] (3) Take 2g of 2% catechol-modified polyvinyl alcohol solution, add 2% nanocellulose at a mass ratio of 1:1 to catechol-modified polyvinyl alcohol, and stir evenly. Add 8mg / mL MXene dispersion at a mass ratio of 1:1 to the mixture to the mixed solution, stir evenly, then put the solution into a mold and freeze it with liquid nitrogen for 1min, then put it into a freeze dryer at a temperature of -65℃ and freeze-dry for 48h to obtain MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel.

[0080] The composite aerogel prepared in the embodiment of the present invention was tested for wave absorption and sound absorption. The wave absorption performance in the X-band was as follows: Figure 2d As shown in FIG. 1 , the reflection coefficient of the device with a thickness of 4.05 mm can reach a minimum of -35.82 dB, and the effective absorption bandwidth can cover the entire X-band (8.2 to 12.4 GHz), which shows that the invention has excellent wave absorption performance; the sound absorption performance exhibited in the frequency range of 1000 Hz to 6300 Hz is as follows: Figure 3 As shown, the sound absorption coefficient of the sample with a thickness of 30 mm is greater than 0.2 dB, which indicates that the invention has good sound absorption performance.

[0081] Example 5

[0082] (1) A few-layer MXene suspension with a certain solid content was centrifuged at 10,000 rpm for 10 min, and part of the supernatant was poured out and shaken evenly to obtain a stable and uniform black suspension. According to the solid content of the few-layer MXene suspension, the volume of the supernatant was adjusted to obtain a few-layer MXene suspension with a concentration of 10 mg / mL.

[0083] (2) Add 1g of polyvinyl alcohol powder to 10mL of dimethyl sulfone (DMSO) and stir at 80°C to completely dissolve it. After cooling to room temperature, add 75mg of 3,4-dihydroxybenzaldehyde (DBA) and 25mg of p-toluenesulfonic acid monohydrate (TsOH), and stir the reaction at 80°C for 12h under nitrogen protection. After the reaction is completed, the mixture is cooled to room temperature, and acetone is added to obtain a precipitate, which is vacuum dried at 45°C for 30min to obtain a catechol-modified polyvinyl alcohol solid. The synthesized catechol-modified polyvinyl alcohol is dissolved in deionized water, stirred at 90°C for 1h, and cooled to room temperature to obtain a 2% catechol-modified polyvinyl alcohol solution.

[0084] (3) Take 2g of 2% catechol-modified polyvinyl alcohol solution, add 2% nanocellulose at a mass ratio of 1:1 to catechol-modified polyvinyl alcohol, and stir evenly. Add 10mg / mL MXene dispersion at a mass ratio of 1:1 to the mixture to the mixed solution, stir evenly, then put the solution into a mold and freeze it with liquid nitrogen for 2 minutes, and then put it into a freeze dryer at a temperature of -62°C for freeze drying for 48 hours to obtain MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel.

[0085] The composite aerogel prepared in the embodiment of the present invention was tested for wave absorption and sound absorption. The wave absorption performance in the X-band was as follows: Figure 2e As shown in FIG. 1 , the reflection coefficient of the 2.55 mm thickness can reach a minimum of -27.51 dB, and the effective absorption bandwidth can cover the entire X-band (8.2 to 12.4 GHz), which shows that the invention has excellent wave absorption performance; the sound absorption performance displayed in the frequency range of 1000 Hz to 6300 Hz is as follows Figure 3 As shown, the sound absorption coefficient of the sample with a thickness of 30 mm is greater than 0.2 dB, which indicates that the invention has good sound absorption performance.

[0086] The composite aerogel prepared in the embodiment of the present invention was subjected to compression-rebound performance test. Figure 5a As shown in the figure, CNF / PVA-CA / MXene-10 composite aerogel (0.08g) can withstand a load of 50g (about 600 times its own weight); after compressing the composite aerogel in the vertical growth direction with a 50g weight and repeating it three times, the compressed shape can be basically restored. In addition, when different degrees of compression (10%, 20% and 30% strain) are applied to the CNF / PVA-CA / MXene-10 composite aerogel in the vertical growth direction, as shown in the figure, Figure 5b As shown in the figure, the stress-strain diagram shows a continuous closed cycle, indicating that the composite aerogel has good compression-rebound performance. Figure 5c As shown in Figure d, the CNF / PVA-CA / MXene-10 composite aerogel was subjected to 800 compression-rebound cycles along the vertical growth direction under 20% strain, and the compression recovery rate of the composite aerogel was still as high as 80%. The test results show that MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel has good structural stability.

[0087] It can be seen from the above examples and related experimental tests that the MXene / nanocellulose / catechol-modified polyvinyl alcohol aerogel prepared by the preparation method of the present invention has good wave absorption performance, sound absorption performance, compression-rebound performance and antioxidant performance.

[0088] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0089] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a composite aerogel containing MXene, characterized in that: The following steps are included: The few-layer MXene suspension is centrifuged and concentrated to obtain few-layer MXene dispersions of different concentrations; Under nitrogen protection, polyvinyl alcohol is acetalized to obtain catechol-modified polyvinyl alcohol. The modified polyvinyl alcohol is dissolved in water to obtain a modified polyvinyl alcohol solution, and the nanocellulose aqueous solution and the few-layer MXene dispersion are added successively. After uniform stirring and mixing, the mixture is poured into a mold and directionally frozen with liquid nitrogen. After vacuum drying, a composite aerogel containing MXene is obtained.

2. The method for preparing a composite aerogel containing MXene according to claim 1, characterized in that: The invention also includes the preparation of a few-layer MXene suspension, which is prepared by etching a MAX phase precursor with LiF-HCl, wherein the MAX phase precursor includes Ti3C2T X Solution, Ti3N2T X Solution, Ti3CNT X Solution or Ti2CT X One or more of the solutions.

3. The method for preparing a composite aerogel containing MXene according to claim 1, characterized in that: The centrifugal speed during the concentration of the few-layer MXene suspension is 10,000 rmp; the centrifugation time is 10-20 min; and the concentration of the few-layer MXene suspension obtained after the centrifugation and concentration is 2-10 mg / mL.

4. The method for preparing a composite aerogel containing MXene according to claim 1, characterized in that: The preparation of the catechol-modified polyvinyl alcohol is specifically to add polyvinyl alcohol powder into dimethyl sulfone, continuously stir and heat it to make it completely dissolved, cool it to room temperature, and then add 3,4-dihydroxybenzaldehyde and p-toluenesulfonic acid monohydrate to carry out acetalization reaction.

5. The method for preparing a composite aerogel containing MXene according to claim 4, characterized in that: The mass ratio of the polyvinyl alcohol, 3,4-dihydroxybenzaldehyde and p-toluenesulfonic acid monohydrate is 1:(0.07-0.08):(0.2-0.3); the acetalization reaction temperature is 80°C.

6. The method for preparing a composite aerogel containing MXene according to claim 1, characterized in that: After the acetalization reaction, the modified polyvinyl alcohol is obtained after acetone precipitation and vacuum drying.

7. The method for preparing a composite aerogel containing MXene according to claim 1, characterized in that: The modified polyvinyl alcohol is dissolved in deionized water at 80° C. to obtain the modified polyvinyl alcohol solution.

8. The method for preparing a composite aerogel containing MXene according to claim 1, characterized in that: The mass fraction of the cellulose-based solution is 1%-2%; the freeze-drying temperature is -50 to -60°C; and the freeze-drying time is 48 to 72 hours.

9. The method for preparing a composite aerogel containing MXene according to claim 1, characterized in that: The mass ratio of the nanocellulose, modified polyvinyl alcohol and MXene is 1:1:2.

Citation Information

Patent Citations

  • Preparation method of MXene / cellulose composite aerogel

    CN109679146A

  • Anti-scouring biological insecticide and preparation method thereof

    CN113678825A

  • Catechol-containing polymer surface-modified MXene, MXene conductive material, and surface-modified MXene conductive material

    KR102692340B1